-3x-6=9x+30

Simple and best practice solution for -3x-6=9x+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-6=9x+30 equation:


Simplifying
-3x + -6 = 9x + 30

Reorder the terms:
-6 + -3x = 9x + 30

Reorder the terms:
-6 + -3x = 30 + 9x

Solving
-6 + -3x = 30 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-6 + -3x + -9x = 30 + 9x + -9x

Combine like terms: -3x + -9x = -12x
-6 + -12x = 30 + 9x + -9x

Combine like terms: 9x + -9x = 0
-6 + -12x = 30 + 0
-6 + -12x = 30

Add '6' to each side of the equation.
-6 + 6 + -12x = 30 + 6

Combine like terms: -6 + 6 = 0
0 + -12x = 30 + 6
-12x = 30 + 6

Combine like terms: 30 + 6 = 36
-12x = 36

Divide each side by '-12'.
x = -3

Simplifying
x = -3

See similar equations:

| 5/12(x-6)=30 | | -17=-5*2+b | | 6x-15x=90+9x | | -5x^2+y^2-19x+y-18=0 | | Y=(3x-2)(x-7) | | Y=(4x-6)(x-5) | | 252=(x+1)x | | 15n^2-17np-4p^2=0 | | y=-5/4*5+5 | | (x+2)2=27 | | -x^2+6-8=0 | | -7z-6=-70 | | N(2+1)=20+34 | | 25+81=a | | 0=-5/4x+5 | | 5/12(x-5)=30 | | z+21=15 | | 70/42 | | 16(2x-8)=4(8x+1) | | -3x+14=14 | | 4a^2-40a+64=0 | | 8+9m-2=7m+14-2m | | 3x+4=6y-24 | | 10x^2-21=x | | 0.4(x+2.4)=-2.96 | | 10y-7y-10=50.45 | | 9=-3x+24 | | 5400-5.5v=1300 | | -1/8x=18 | | x^2+3x=-11 | | 4p+6p=20 | | 9=-3+24 |

Equations solver categories